2018
DOI: 10.3102/0162373718787917
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School SES on Student Achievement: Evidence From U.S. Statewide Achievement Data

Abstract: After the U.S. Supreme Court restricted the use of race in assigning students to schools, there was a surge in advocacy of school integration based on student socioeconomic status (SES). Benefits of socioeconomic integration have been supported by various studies finding significant effects of school SES on achievement after controlling for individual student SES. This article investigates school SES effects using statewide longitudinal achievement data from several U.S. states. School SES effects nearly vanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Marks and colleagues (Armor et al, 2018;Marks, 2010Marks, , 2015Marks, , 2017 have critiqued school compositional research for ecological fallacies and lack of control for prior achievement but have rarely engaged with specific studies. The ecological fallacy is when a relationship observed at the group level is mistakenly used to describe the effect of group membership on individuals (Robinson, 1950).…”
Section: Critiques Of Prior School Compositional Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Marks and colleagues (Armor et al, 2018;Marks, 2010Marks, , 2015Marks, , 2017 have critiqued school compositional research for ecological fallacies and lack of control for prior achievement but have rarely engaged with specific studies. The ecological fallacy is when a relationship observed at the group level is mistakenly used to describe the effect of group membership on individuals (Robinson, 1950).…”
Section: Critiques Of Prior School Compositional Researchmentioning
confidence: 99%
“…Marks and colleagues (Armor et al, 2018;Marks 2015Marks , 2017 have also argued that many school compositional studies have overestimated SEC effects by not controlling for prior achievement. This criticism has not considered the differing aims of longitudinal and cross-sectional compositional research.…”
Section: Critiques Of Prior School Compositional Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…At the school/collective level, at least two mechanisms have been proposed to explain why high SES schools tend to perform better than lower SES ones (Armor, Marks, & Malatinszky, 2018;van Ewijk & Sleegers, 2010). The first mechanism operates through school or institutional factors.…”
Section: Educational Equitymentioning
confidence: 99%
“…12 Finally, a new study published in a leading education policy journal analyzed student test scores and socioeconomic status from three statewide databases and found that school economic integration had virtually no effect on math or reading scores once individual socioeconomic status was taken into account. 13 To illustrate these various arguments, we shall examine several case studies of large school districts that adopted socioeconomic integration plans, most of which used controlled-choice methods. These districts are Wake County, North Carolina; Jefferson County, Kentucky; Lee, Manatee, and St. Lucie counties, Florida; and Charlotte-Mecklenburg County, North Carolina.…”
Section: The Policy Debatementioning
confidence: 99%